ANALISIS KETERSEDIAAN SARANA-PRASARANA PENDIDIKAN DAN KESIAPAN IMPLEMENTASI KURIKULUM 2013 DI KABUPATEN TABALONG - Susanto, Heri (Vidya Karya Jurnal Kependidikan, 2015)
The implementation of 2013 Curriculum brought some consequences, one of them is the school should have a good carrying capacity for the implementation of the curriculum. Ideally, scientific approach that used in 2013 Curriculum should be supported by adequate infrastructure. The main reason is in this curriculum students should be required to acquire knowledge through exploratory activities in the learning process and not only received from teacher. This study aimed to determine the availability of educational infrastructure and linkages with the readiness of 2013 Curriculum implementation. This study used mixed methods approach. The result of this study show that more than 95% of schools in Tabalong had not fulfilled the minimum requirements of education infrastructure as required under The 24th Regulation of National Education Ministry Year 2007 about the infrastructure of education. The lack of infrastructure has shown the lack of schoolsâ readiness to organize learning with scientific approach as the implementation of 2013 Curriculum.